Fragmentação florestal, perda de habitat e ocorrência de primatas na Mata Atlântica - Martinelli, Flávia Silva (2014)
Habitat loss and fragmentation are threats to biodiversity, which means global conservation concerns, and it is responsible to many species extinction but animal species do not respond to these threats in the same manner. To face this threatening and propose solutions, many studies have focused on analyze the effects of them on biodiversity. However, few variables are used to try to answer how fragmentation affects primates and little is known about relationship between habitat features and primates of southeast Atlantic Forest. We obtained primate data via interviews with local people of Santa Maria de Jetibá countryside and using data from Muriqui – ES Project to investigate the relationships between presence of primates and habitat parameters in 35 forest fragments southern of Brazil. We detected 6 primate species: Alouatta guariba, Callicebus personatus, Callithrix flaviceps, Callithrix geoffroyi, Brachyteles hypoxanthus and Sapajus nigritus. In addition, we assessed fragment size and fragment shape, besides percentage of habitat, surrounding forest area and number of fragments to measure fragmentation inside a 2 km buffer. Fragment metrics were extracted from a 2008 aerial photos using Geographic Information Systems and remote sensing, and then we examined the best predictor to species persistence. We use simple and multiple regressions to investigate what we propose to, and the best models were selected by Akaike Information Criterion. Total species number is correlated with forest size, as expect for species-area relationship (SAR) studies. Percentage of habitat surrounding the fragment also contributes to species richness, in opposite to number of fragments in surrounding area that we used to the measure fragmentation. A. guariba was present in all fragments and his occurrence did not correlate with any of the habitat variables assessed, revealing high ecological plasticity. The probability of finding B. hypoxanthus, increases as larger is fragment size and the greater the percentage of surrounding habitat. The same was found to S. nigritus, C. personatus and Callithrix spp., probably for different reasons since they are very distinct species. This study contributes is the first study that relates landscape metrics with the occurrence of certain primate species of the Atlantic Forest and provides important baseline data for specific conservation measures for the individual context of each species and for future studies involving the landscape.